Self Regulated Learning Dan Manajemen Waktu Pada Mahasiswa Tingkat Akhir Yang Bekerja Freelance - Mita Amalia, Shaffina; Arief Setiawan, Nugroho; Hidayati, Ira; Zarkasi, Ahmad (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2026)
Final-year students face complex academic demands, such as completing their thesis, while some simultaneously engage in freelance work to meet economic needs and gain professional experience. This condition requires optimal self-management skills to maintain a balance between academic responsibilities and work commitments. This study aims to examine the implementation of Self-Regulated Learning (SRL) among final-year students who work freelance in Bandar Lampung, focusing on metacognitive, motivational, and behavioral aspects. This research employs a qualitative approach with a case study design and methodological triangulation through interviews and documentation involving three informants. Data were analyzed using NVivo 15 to identify patterns of SRL implementation. The findings indicate that students are able to apply planning, monitoring, and self-evaluation strategies in their learning process, although they still face challenges such as time constraints, fatigue, and inconsistency in managing their learning activities. The consistent application of SRL strategies helps students manage both academic and work responsibilities more effectively. Therefore, SRL plays a crucial role in supporting students in balancing academic demands and freelance work. Keywords: Self Regulated Learning, time management, freelance students, learning strategies, work and academic balance.